If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6=h/18
We simplify the equation to the form, which is simple to understand
-6=h/18
We move all terms containing h to the left and all other terms to the right.
-0.055555555555556h=+6
We simplify left and right side of the equation.
-0.055555555555556h=+6
We divide both sides of the equation by -00.055555555555556 to get h.
h=-108
| (7x-6)=6-7x | | 5x+17=5x+98 | | X^3-48=4x | | 30+8n=4(2n+7) | | x=2x-73 | | m+1.89=6.519 | | 7(x+4)=3(x+2) | | -6(1+7k)-5=-4K+27 | | -3t+6=60 | | 9p+5=-12 | | 3-5*4= | | -(6x+8)=-8-6x | | 8.2x=10.66 | | -5x+2x=-12 | | 4x+x-3=2 | | 0.3(x+20)-0.05(x-10)=21.5 | | g(x)=17x^9+1 | | y=5x+150 | | (17x-7)+20x+15x+(12x-17)=360 | | 24+4b=6(b+2) | | u=4(2n+33)+5(n+1) | | 2(3z+1)-(2-6)= | | f(0.03)=3x^3-2x^2+6x-4 | | a=(5x-3)(x+2)(2x+3)(3x-2) | | 7-4x=x-8 | | -6+7x=6x-6 | | 2w+w+2w+1=76 | | sin(180)= | | 15.1r=8.9 | | 3p^2-17=0 | | a=(5x-3)(x+2) | | 3x^2+2x=2x+27 |